TYPOLOGICAL INTERPRETATION OF LINGUACULTURAL FEATURES OF FAMILY VOCABULARY OF RUSSIAN, UZBEK AND ENGLISH LANGUAGES - Usmonova Gulchehra Omonovna (Bright Mind Publishing, 2025)
Family is the oldest social group of people related to blood relatives. The name of this ethnic group can be called by other names in different languages of the world, but the meaning and significance should not be underestimated. Language and culture form different mentalities and theories, so there are many features of the family concept in the East and West. Features of the family concept in English and Uzbek families is an interesting topic for studying the language sphere. This article examines the role of the family in both Western and Eastern countries. Family vocabulary is a very important element of speech communication, oral or written, digital or religious. It plays an important role in the process of historical development of language. This continuous process has been used since ancient times, so this study provides a strategy for speech communication among family and friends for successful speech communication.
Keywords: Family vocabulary, linguistic and cultural features, respect, gender, mahalla, proverbs, elderly people, ethics introduction how to behave near the dostarhan, religion, mentality and others.